EFL STUDENTS' READINESS ON THE IMPLEMENTATION OF ENGLISH COURSE IN ELEMENTARY SCHOOL: A STUDY AT ELEMENTARY SCHOOL 119 JAMBI CITY - Ananda, Arani Tri (Langue (Journal of Language and Education), 2022)
This study explored the students’ readiness in term of preparation, experience, difficulties, and overcome the difficulties on the implementation of English as course in accordance to Merdeka Belajar Curriculum. This study was a qualitative research with a case study approach. The main data was obtained qualitatively from focus group discussion with 10 grade 4 students. The site of this was at Elementary School 119 Jambi City. The focus group discussion was conducted face-to-face in Indonesian, audio-taped, and directly transcribed. The data analyzed through reading the transcribed transcriptions. Through this research, the researcher found out aside some of the difficulties the students feel ready to learn English as a course at Elementary School 119 Jambi City because of the positive relationship teacher-students, students-students, students-school environment. Then, the students’ self-directed learning motivation and supportive environment helped the students in English language learning.